Teachers’ Understanding in the Implementation of Project Based Learning (PjBL) Model in ‘Kurikulum Merdeka’ - Heni Rita Susila; Edi Sutiono; Anisya Julia Putri (Akademika : Jurnal Teknologi Pendidikan, 2024)
The purpose of this study was to determine the understanding of vocational high school teachers regarding the implementation of project-based learning models or known as project based learning (PjBL). The PjBL model has become an important part of the independent curriculum because this learning model is closely related to the concept of independent learning to provide flexibility to students. This learning model is also one of the learning models recommended for use in the independent curriculum. This research was conducted by distributing questionnaires to collect information about teachers' understanding of the PjBL model. The respondents of this study were 64 vocational high school teachers. The data was analyzed quantitatively using percentages. Researchers collected information using indicators from front-end analysis introduced by Lee Owen. These indicators are audience analysis, technology analysis, critical-incident analysis and media analysis. The highest score with a percentage of 87% stated that teachers wanted to develop a video-based media that simulated the implementation of the project based learning (PjBL) learning model.